Treatment with aldose reductase inhibitor or with myo-inositol arrests deterioration of the electroretinogram of diabetic rats. - MacGregor, L C (1985)
Biochemical abnormalities in the retinal pigment epithelium of experimentally diabetic animals include increased sorbitol and decreased myo-inositol. Diabetes also causes a progressive reduction in the amplitude of the c-wave of the electroretinogram of the pigmented rat. The c-wave is generated by the retinal pigmented epithelium. Myo-inositol administration or treatment with sorbinil, an inhibitor of aldose reductase, arrested the decline in the c-wave. Therefore, hyperglycemia-associated defects in myo-inositol or sorbitol metabolism may be involved in the pathogenesis of the electrophysiological deficit of the diabetic retina. The homogeneous cell layer of the pigment epithelium may be a useful tissue model for studying the pathogenesis of the complications of diabetes.